Synthesis and biological activity of thieno[3, 2-d]pyrimidines as potent JAK3 inhibitors for the treatment of idiopathic pulmonary fibrosis. Issue 2 (15th January 2020) - Zhu, Yanming; Zheng, Xu; Wang, Changyuan; Sun, Xiuli; Sun, Huijun; Ma, Tengyue; Li, Yanxia; Liu, Kexin; Chen, Lixue; Ma, Xiaodong
Graphical abstract: Abstract: Idiopathic pulmonary fibrosis (IPF) is a serious and fatal lung disease, with a median survival of only 3–5 years from diagnosis. Janus kinase 3 (JAK3) has a well-established role in the pathogenesis of various autoimmune diseases, including rheumatoid arthritis (RA) and autoimmune-related pulmonary fibrosis. In this study, through the use of a conformationally-constrained design strategy, a series of thieno[3, 2- d ]pyrimidines were synthesized as potent JAK3 inhibitors for the treatment of IPF. Among them, the most potent JAK3 inhibitor, namely 8e (IC50 = 1.38 nM), significantly reduced the degree of airsacculitis and fibrosis according to hematoxylin-eosin (HE) staining assay for the lung tissue in the bleomycin (BLM)-induced pulmonary fibrosis mouse model. The clear reduction of the lung collagen deposition by the determination of Masson and hydroxyproline (HYP) content also demonstrated its efficacy in the treatment of fibrosis. In addition, 8e also reduced the expression of the inflammatory markers IL-6, IL-17A, TNF-α and malondialdehyde (MDA) in lung tissue, which indicated its higher anti-inflammatory activity compared with that of the reference agents (nintedanib and gefitinib). Furthermore, it possessed low cytotoxicity against normal human bronchial epithelia (HBE) cells (IC50 > 39.0 μM) and C57BL mice. All these evaluated biological properties suggest that 8e may be a potential JAK3 inhibitor for the treatment of IPF.